Impact of atrial fibrillation type (paroxysmal vs. non-paroxysmal) on long-term clinical outcomes: The RAFFINE registry subanalysis. Issue 5 (May 2023) - Wada, Hideki; Miyauchi, Katsumi; Suwa, Satoru; Miyazaki, Sakiko; Hayashi, Hidemori; Yamashiro, Kazuo; Tanaka, Ryota; Nishizaki, Yuji; Nojiri, Shuko; Sumiyoshi, Masataka; Nakazato, Yuji; Urabe, Takao; et al.
Abstract: Background: The type of atrial fibrillation (AF) (paroxysmal or non-paroxysmal) is important in determining its therapeutic management. However, the prognostic impact of AF type on the incidence of cardiovascular events remains uncertain. Methods: We investigated patients with AF who were selected from an observational, multicenter, prospective registry (RAFFINE) comprising 4 university hospitals and 50 general hospitals/clinics in Japan between 2013 and 2015. In this subanalysis study, patients were divided into two groups according to their AF pattern at the time of enrollment. The primary outcome was the composite of death, ischemic stroke, and heart-failure-related hospitalization. Results: Among 3845 patients, 1472 (38.3 %) and 2373 (61.7 %) had paroxysmal and non-paroxysmal type AF, respectively. Patients with non-paroxysmal AF were older and had higher CHADS2 score and prevalence of comorbidities. During median follow-up of 3.7 years, 681 (17.7 %) primary endpoints were identified. Cumulative incidences of the primary endpoint were significantly higher in the non-paroxysmal AF group; however, rates of bleeding events were not significantly different between the groups. Multivariate Cox hazard analysis showed that non-paroxysmal AF had significantly higher risk of cardiovascular events compared with paroxysmal AF (hazard ratio, 1.38; 95 % confidence interval, 1.17–1.64; p = 0.0002). Conclusions: Non-paroxysmal AF was significantly associated with cardiovascular events. Long-term clinical outcomes might be improved if transition from paroxysmal to non-paroxysmal AF can be prevented. Graphical abstract: Unlabelled Image Highlights: The aim was to evaluate the prognostic impact of atrial fibrillation (AF) type on clinical outcomes. Clinical risk profile was worse in the non-paroxysmal AF group. Cardiovascular events were more common in the non-paroxysmal AF group. Even when adjusted for risk factors, AF type was associated with clinical outcomes.